Oxytocin and bone status in men: analysis of the MINOS cohort. Issue 12 (December 2015) - Breuil, V.; Fontas, E.; Chapurlat, R.; Panaia-Ferrari, P.; Yahia, H.; Faure, S.; Euller-Ziegler, L.; Amri, E.; Szulc, P.
Abstract Summary Oxytocin, a neurohypophysial hormone, regulates bone metabolism in animal studies and postmenopausal women. In men, oxytocin is not associated with bone mineral density, bone turnover markers, or prevalent fractures, but weakly negatively with incident fragility fracture requiring further studies. Introduction We previously showed that serum oxytocin (OT) level is associated with bone mineral density (BMD) and bone turnover rate in postmenopausal women. The aim of our study was to assess the relationship between circulating OT levels and bone status in men. Methods In 552 men aged 50 and older from the MINOS cohort, we measured serum levels of OT. We assessed the association of serum OT levels with BMD (lumbar, femoral neck, total hip), bone turnover markers (BTM) (serum N-terminal propeptide of type I procollagen (PINP), bone-specific alkaline phosphatase (bone ALP), and C-terminal telopeptide of type I collagen (CTX-I)) and fracture risk. Results In the univariate analysis, serum OT level was not associated with BMD at any site, BTM levels, or with prevalent or incident fracture. OT was significantly correlated with body mass index (BMI) (r  = 0.17, p  < 0.001), total or bioavalaible 17β-estradiol (r  = 0.09, p  = 0.04 andr  = 0.20, p  < 0.001, respectively), free testosterone (r  = 0.17, p  < 0.001), and leptin (r  = 0.16, p  < 0.001). Multivariate analysis did not show significant relationship between serum OT and BMD. After adjustment for age, BMI, interaction BMI/age, history of fall in the last year, and BMD, OT and prevalent fracture were not associated. By contrast, the same analysis with additional adjustment for prevalent fracture showed a weakly significant negative association between OT and incident fracture, e.g., after adjustment for femoral neck BMD, HR = 0.73, 95 %CI 0.55–0.99, p  = 0.04. Conclusion In men, serum OT levels are not associated with BMD, bone turnover rate, or prevalent fractures. The weak negative relationship with fracture risk requires further studies.